History of the Islamic peoples : - Brockelmann, Carl (G. P. Putnam's Sons, 1947)
This book introduce about rise and development of the Islamic peoples and states is described here with vididness, clarity, consiseness, and skill. The results of the latest research have been taken into account. The whole of this vast material is logically and usefully organized.